The American Cyrus: How an Ancient King Became a Political Tool for Voter Mobilization - Trangerud, Hanne Amanda (Religions, 2021)
During the 2016 presidential election, Evangelical supporters of Donald Trump presented him as a modern version of the ancient King Cyrus of Persia. To many conservative Christians, the comparison offered a justification of voting for a candidate whose character supposedly was at odds with their Christian virtues. Subsequent to his inauguration, the idea of Trump being an American Cyrus continued to develop and circulate. It is the aim of this article to deepen the understanding of Cyrus as a political tool in the West and explain how he ended up as a means to mobilize American voters. With an emphasis on the last 250 years, the article looks at how various personalities have been compared to Cyrus or presented as modern Cyruses. Based on these examples, it develops a typology, arguing that the modern Cyrus can be best understood as different types and subtypes, of which several have been applied to Trump. The article demonstrates how the various subtypes have separate evolutionary lines, which in turn can be attributed to different goals and functions.